Experimenting Dance Content for Historical Pedagogy in Nigeria: Lessons From the Imo State University Experience - Abakporo, Princewill Chukwuma; Ohenhen, Stanley Timeyin; Egbe, Fidelis Enang; Ofoedu, Uche Okey; Кhafizova Mashkhura Aminovna; Kondrla, Peter (Journal of Education Culture and Society, 2025)
Aim. In response to recent calls from scholars and cultural officers to resuscitate indigenous dances and other indigenous markers in Nigeria, this study aimed at exploring novel ways to revamp the content, teaching methods and appeal of indigenous dances in higher institutions in Nigeria. The project relied on a practical experiment at Imo State University, Nigeria to unveil how a vibrant and sustained indigenous dance tradition might be utilised as alternative pedagogical tool for history lessons which was excluded from the secondary school curriculum in 2009. Methods. The performance project utilised dance in retelling the highpoints of Nigeria’s history from precolonial to postcolonial period. It utilised movements and rhythm to capture the highpoints of historical happenings within the periods of focus. Unstructured interviews, participant observation, case study approaches were utilised in data collection, while critical pedagogy, positive psychology, flow theory, and somatics were also adopted as methodological and analytical use in the project. Results. From the dance experiment, the researchers observed that teaching approaches have always been at the heart of students’ disinterest in dance courses in most Nigerian universities. They also noted that the potentials and appeal of indigenous dance be heightened when new realities are injected into its contents and a more liberal and inclusive approach adopted in the teaching and learning process. Conclusion. In conclusion, key areas to revitalising and sustaining the appeal of indigenous dances among students include rethinking old pedagogical approaches by incorporating emerging/prevailing sociological realities into indigenous dance creations and performance in contemporary times.